P.058 Tuberous sclerosis complex associated intracranial abnormalities identified in utero via antenatal ultrasound. (5th June 2019) - Hanes, IE; Abdeen, N; Muir, K; Sell, E
Abstract : Background: Tuberous sclerosis complex (TSC) is characterized by growth of benign tumors in the skin, brain, kidneys, lung and heart. Prognosis is mostly determined by the extent of brain involvement as tumors in the brain lead to seizures and cognitive problems. Epilepsy is highly associated with the cognitive abnormalities in TSC and recent evidence suggests anti-epileptic treatment before onset of seizures reduces epilepsy severity and risk of mental retardation. Screening and potential identification of TSC in utero via ultrasound would allow for prophylactic seizure management in these children. The sensitivity of antenatal ultrasound in the identification of brain abnormalities associated with TSC has not yet been published. In this case, we review the antenatal ultrasounds of a child with TSC for evidence of brain abnormalities in utero.Methods: Retrospective reviewResults: Retrospective review of antenatal ultrasounds showed some evidence of intracranial abnormalities. Ultrasound at 34 weeks and 4 days gestation revealed an echogenic density in the right ventricle that correlates with SEGA on post-natal MRI brain at 12 days of life. Post-natal brain ultrasound at 37 weeks revealed multiple cranial abnormalities not seen in utero.Conclusions: There are limitations to antenatal neurosonography in the detection of intracranial abnormalities associated with TSC.